Neutrophil Extracellular Trap-Associated Protein Activation of the NLRP3 Inflammasome Is Enhanced in Lupus Macrophages - Kahlenberg, J. Michelle (2012)
Neutrophil extracellular traps (NETs) represent an important defense mechanism against microorganisms. Clearance of NETs is impaired in a subset of patients with systemic lupus erythematosus (SLE), while NETosis is increased in neutrophils and, particularly, in low-density granulocytes derived from lupus patients. NETs are toxic to the endothelium, expose immunostimulatory molecules, activate plasmacytoid dendritic cells and may participate in organ damage through incompletely characterized pathways. In order to better understand the role of NETs in fostering dysregulated inflammation, we examined inflammasome activation in response to NETs or to LL-37, an antibacterial protein externalized on the NETs. Both NETs and LL-37 activate caspase-1, the central enzyme of the inflammasome, in both human and murine macrophages, resulting in release of active IL-1β and IL-18. LL-37 activation of the NLRP3 inflammasome utilizes P2×7 receptor-mediated potassium efflux. NET and LL-37-mediated activation of the inflammasome is enhanced in macrophages derived from lupus patients. In turn, IL-18 is able to stimulate NETosis in human neutrophils. These results suggest that enhanced formation of NETs in lupus patients can lead to increased inflammasome activation in adjacent macrophages. This leads to release of inflammatory cytokines which further stimulate NETosis, resulting in a feed-forward inflammatory loop that could potentially lead to disease flares and/or organ damage.